Cidadania laboral e a efetivação dos direitos fundamentais nas relações de trabalho - Molina, Ananda Elisa dos Santos Sommier (2019)
The present research proposes a reflection on the human relations established in the workplace, starting from a brief analysis about Fundamental Rights and its effectiveness in private relations. From the demonstration of the mutability of this list of rights, a parallel is drawn with labor relations, whose regulation often ends up in the possible compositions in this environment, at the initiative of the parties involved. Through the study on the empowerment of workers in their work environment, we sought to understand how the exercise of citizenship, in its universal sense of accomplishment, can be admitted as a vector of effectiveness of fundamental rights, thus enabling the social transformation of being